Stable preservation and recovery of methylation marks from FTA elute cards in species with nucleated red blood cells using a customized DNA extraction method - Livia Gerber; Sarah L. Whiteley; Erin E. Hahn; Clare E. Holleley (PLoS ONE, 2025)
Specialized chemically-coated paper cards, such as Flinders Technology Associates (FTA) cards, provide simple and reliable storage of nucleic acids by protecting DNA from degradation. Owed to their simplicity, FTA cards are widely used in clinical testing, forensic science and specimen archives. Originally developed for PCR-based applications that only require short DNA fragments, FTA cards are now being explored as an avenue for whole-genome and epigenetic sequencing applications. FTA cards and their corresponding DNA extraction protocols have not kept pace with advances in sequencing technologies. Because the initial protocols developed for FTA cards were geared towards applications using PCR amplification of short fragments, they typically yield low molecular weight DNA. This issue is particularly pronounced for FTA elute cards where heat-based elution at 95°C leads to DNA denaturation and fragmentation. Isolation of DNA from nucleated blood deposited onto FTA elute cards poses an additional challenge when compared to FTA classic cards, because hemoglobin is irreversibly bound to the card matrix, making the majority of DNA present in nucleated blood inaccessible. Here, we describe an easy, fast, and inexpensive protocol to extract high molecular weight DNA (>10 kb) of nucleated blood stored on FTA elute cards suitable for most genomic library preparations including those that interrogate DNA methylation. Our protocol yields a 14-fold increase in yield compared to numerous alternatives. Using our protocol, we demonstrate that high molecular weight DNA can still be extracted even after storage at ambient temperature for over a decade. Moreover, we show that DNA methylation marks are preserved on FTA elute cards, broadening the utility of FTA elute cards. This opens possibilities for (epi-)genomic studies using historical samples and enabling specimen collection where access to chemicals or cryogenic storage is limited – reducing project costs and extending collection opportunities into remote areas.